3D printing material composition and processing method
Patent Information
- Application Number
- CN202511088973.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2025-04-02
- Filing Date
- 2025-08-05
- Publication Date
- 2026-10-16
AI Technical Summary
但由于3D打印混凝土件和钢筋之间的收缩不匹配,导致两者界面出现应力集中,这可能会导致更多的裂缝
[0048]本发明具有以下优点:
Smart Images

Figure CN122916533A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to a 3D printing material and its preparation method. More particularly, this invention relates to a 3D building printing material composition using recycled aggregates and its processing and preparation method. Background Technology
[0002] 3D printing technology has been widely applied in urban development and construction. With the development of building technology, especially unmanned building technology, 3D printing technology has been widely used in the construction industry. 3D printing technology, also known as 3D architectural printing, refers to the automated process of manufacturing building elements or entire structures using a 3D printer. The 3D printing material used in construction does not use ink; instead, it involves printing concrete material layer by layer, which is why 3D architectural printing is also called additive manufacturing or additive construction. Concrete components of different shapes and structures are printed through specific computer-controlled programs. The entire process of computer programming and mechanized construction allows for the unification of architecture, structure, and construction. Furthermore, 3D printing construction technology can be carried out both indoors and outdoors.
[0003] In the construction industry, even with 3D printing, concrete remains the most widely used material. The application of concrete in urban development not only requires the large-scale extraction of natural sandstone resources but also damages mountain vegetation and waterways. Therefore, recycling waste concrete and using it as recycled aggregate for future development solves the problem of large quantities of difficult-to-dispose waste concrete and the gradual deterioration of the ecological environment due to these difficulties. However, compared to natural aggregates such as quartz sand, recycled aggregates have a rougher surface and higher porosity.
[0004] Untreated recycled aggregates may result in higher water absorption, affecting their printability in 3D printing materials, such as buildability, extrudability, and pumpability, leading to reduced flexural and compressive strength and increased dry shrinkage. Low mechanical properties will result in potential damage during transportation and use; the high dry shrinkage of 3D-printed concrete parts may cause cracking during hydration or at low outdoor temperatures. In particular, when printing prototypes with spans exceeding 1 meter, the relatively low flexural strength makes them more likely to deform or develop larger cracks during handling. Therefore, it is necessary to reinforce the structure with steel reinforcement. However, due to the shrinkage mismatch between the 3D-printed concrete parts and the steel reinforcement, stress concentration occurs at the interface, which may lead to further cracking. Summary of the Invention
[0005] To overcome the shortcomings of the prior art, this invention proposes a method for surface treatment of recycled aggregates to improve overall quality consistency and reduce water absorption. Furthermore, the aggregate particle size used in the 3D printing material of this invention has been optimized. Therefore, the 3D printing material formulation developed in this invention exhibits good printability and contains up to 30% recycled aggregate. This formulation demonstrates ideal properties, such as improved mechanical properties, reduced shrinkage, low water absorption, and good fire resistance. Moreover, based on the optimized formulation, this invention has successfully printed and implemented various concrete prototypes, such as currently used flower pots (up to 1.5 meters long) and benches (up to 2 meters long).
[0006] This invention provides a 3D-printed concrete formulation using recycled aggregate, comprising at least 30% recycled aggregate to replace conventional aggregate, and incorporating a surface treatment method. This invention also provides a 3D printing material composition comprising a cementitious binder, aggregate, water, and admixtures. Specifically, the aggregate comprises recycled aggregate and quartz sand, and the recycled aggregate is treated with a water-soluble polymer. The water-soluble polymer is a polyvinyl alcohol (PVA) solution. In this embodiment, the PVA solution has a weight percentage concentration of 5 wt% to 15 wt%.
[0007] Preferably, water accounts for 10% to 20% of the total weight of the composition. The cement-based binder accounts for 20% to 40% of the total weight of the composition, and includes 50% to 70% cement. Recycled aggregate accounts for 10% to 30% of the total weight of the composition, and wherein recycled aggregate accounts for more than 30% of the total aggregate. Quartz sand accounts for 25% to 40% of the total weight of the composition.
[0008] Preferably, the particle size range of each recycled aggregate is best from 0.3 mm to 2.36 mm. The particle size of each quartz sand is from 0.3 mm to 0.6 mm.
[0009] In one embodiment, the cement-based binder comprises fly ash (FPA), silica fume (SF), and / or ground granulated blast furnace slag (GGBS).
[0010] In one embodiment, the admixture comprises a superplasticizer, a thixotropic agent, a viscosity modifier, a retarder, and a swelling agent. The swelling agent is a low-dose swelling agent, such as HPCSA (CSA powder manufactured by Denka).
[0011] This invention provides a method for processing a 3D printing material composition, the steps of which include: (a) Provide a 5wt% to 15wt% polyvinyl alcohol (PVA) solution; (b) Mix the recycled aggregate with a 5 wt% to 15 wt% PVA solution and soak the mixed recycled aggregate for at least 24 hours; (c) The air-dried and mixed recycled aggregate is left to dry for at least 7 days to form treated recycled aggregate; (d) Mixing treated recycled aggregates with cementitious binders, aggregates, water and admixtures to form a composition of 3D printing materials.
[0012] Preferably, the 5wt% to 15wt% PVA solution is prepared by mixing PVA powder with water at 90°C to 100°C. The mixed recycled aggregate is then air-dried at 20°C.
[0013] Preferably, the particle size of each recycled aggregate is preferably in the range of 0.3 mm to 2.36 mm. The recycled aggregate accounts for more than 30% of the aggregate and the recycled aggregate in the optimal total weight ratio. Attached Figure Description
[0014] Figure 1 The figures show the compressive strength test results of three groups of 3D printed concrete parts and their corresponding cast specimens in three dimensions in an embodiment of the present invention.
[0015] Figure 2 The figures show the flexural strength test results of three groups of 3D printed concrete parts in the two-dimensional direction and their corresponding cast specimens in an embodiment of the present invention.
[0016] Figure 3 The figures show the water absorption test results of three groups of 3D printed concrete parts according to ASTM C642 in an embodiment of the present invention.
[0017] Figure 4 The figures show the shrinkage test results of three groups of 3D printed concrete parts in an embodiment of the present invention.
[0018] Figure 5 The figure shows the tensile strength test results of three groups of 3D printed concrete parts after 28 days of bonding in an embodiment of the present invention.
[0019] Figures 6A to 6D This is a schematic diagram illustrating the effect of PVA solution treatment on the 3D printing material composition in this invention.
[0020] Figure 7 This is a flowchart of the processing method for the 3D printing material composition in this invention.
[0021] Figure 8Aand Figure 8B The images are SEM images of general recycled aggregate and recycled aggregate treated with PVA solution, respectively.
[0022] Explanation of icon numbers C. Old cement matrix GGBS Slag Powder O Old aggregate OPC ordinary Portland cement PVA membrane or agglomeration state PFA fly ash Detailed Implementation
[0023] Those skilled in the art will understand that the execution order of the steps included in the methods provided in the embodiments of the present invention may not necessarily follow the order shown in the embodiments. Unless there is a specifically stated dependency relationship between the steps, the present invention does not limit the execution order of the steps. Furthermore, other steps may be inserted between the steps without affecting the spirit of the present invention. Such derived practical examples will also fall within the scope of the present invention.
[0024] This invention relates to a composition for 3D printing materials and a method for processing the composition. More specifically, this invention relates to a composition using recycled aggregate and a method for surface treatment of recycled aggregate for 3D printing materials.
[0025] This invention proposes a 3D-printed concrete formulation using recycled aggregate, comprising at least 30% recycled aggregate and incorporating a surface treatment method for the aggregate. Untreated recycled aggregate may result in relatively high water absorption, affecting its printability in 3D printing materials, such as buildability, extrudability, and pumpability, leading to reduced mechanical strength and increased dry shrinkage. Low mechanical properties can cause potential damage during transportation and use; the high dry shrinkage of 3D-printed concrete parts may cause cracking during hydration or at low outdoor temperatures. In particular, when printing prototypes with a span exceeding 1 meter, the relatively low flexural strength makes them more susceptible to deformation or larger cracks during handling. Therefore, it is necessary to reinforce the structure with steel reinforcement. However, the shrinkage mismatch between the 3D-printed concrete parts and the steel reinforcement leads to stress concentration on both, which may result in even more cracking.
[0026] To address the aforementioned challenges, this invention proposes a method for surface treatment of recycled aggregates to improve overall quality consistency and reduce water absorption. Furthermore, the aggregate particle size is also optimized. Therefore, the 3D printing material formulation developed in this invention utilizes up to 30% recycled aggregates, resulting in significantly improved printability. This formulation exhibits desirable properties, such as improved mechanical properties, reduced shrinkage, lower water absorption, and good fire resistance. Moreover, based on the optimized formulation, this invention has successfully printed and implemented various concrete prototypes, such as currently used flower pots (up to 1.5 meters long) and benches (up to 2 meters long).
[0027] Those skilled in the art will understand that various combinations of embodiments of the present invention can be combined to provide a 3D-printed concrete formulation using recycled aggregate, the formulation comprising more than 30% recycled aggregate, and combined with a processing method. Embodiments of the present invention provide a 3D printing material composition comprising a cementitious binder, aggregate, water, and admixtures. Specifically, the aggregate comprises at least recycled aggregate and quartz sand, and the recycled aggregate is treated with a water-soluble polymer. The water-soluble polymer is a polyvinyl alcohol (PVA) solution. In an embodiment of the present invention, the weight percentage concentration of the PVA solution is 5 wt% to 15 wt%.
[0028] Preferably, water accounts for 10% to 20% of the optimal total weight percentage of the composition. The cement-based binder accounts for 20% to 40% of the total weight percentage of the composition and contains 50% to 70% ordinary Portland cement. Recycled aggregate accounts for 10% to 30% of the total weight percentage of the composition, and the recycled aggregate accounts for more than 30% of the total aggregate weight. Quartz sand accounts for 25% to 40% of the total weight percentage of the composition.
[0029] Large-diameter recycled aggregates are relatively easy to collect and beneficial for future commercialization. Preferably, the optimal particle size of each recycled aggregate in this invention is 0.3 mm to 2.36 mm. The particle size of each quartz sand is 0.3 mm to 0.6 mm.
[0030] In one embodiment, the cementitious binder comprises fly ash (FPA), silica fume (SF), and / or ground granulated blast-furnace slag (GGBS). In another embodiment, the admixture comprises a superplasticizer, a thixotropic agent, a viscosity modifier, a retarder, and an expansive agent. The expansive agent is a low-dosage expansive agent, such as HPCSA (CSA powder manufactured by Denka).
[0031] As shown in Table 1, three examples of 3D-printed concrete parts (control group 1, control group 2, and the present invention example) are compared below. They are all prepared using the same method and 3D printing process. The recycled aggregate (RA) in the table below was collected from K. Wah Building Materials Company in Hong Kong, China.
[0032] Table 1
[0033]
[0034] Control group 1 was a reference group that did not contain recycled aggregate.
[0035] Control group 2 consisted of 30% recycled aggregate with a particle size of 0.3-2.36 mm.
[0036] The example is a 3D printed concrete part made from the 3D printing material composition implemented according to the present invention, which contains 30% recycled aggregate with a particle size of 0.3-2.36 mm, and the aforementioned recycled aggregate has been surface treated with a PVA solution with a weight percentage concentration of 5-15 wt%.
[0037] The following is an explanation of the abbreviations in Table 2: OPC is a type of ordinary silicate cement (originating from Qingzhou Yingni); PFA stands for fly ash (originating from Yingni, Qingzhou). GGBS is slag powder (derived from Qingzhou Yingni); RA is recycled aggregate (sourced from K. Wah Building Materials, Hong Kong). Gel 208 is a thixotropic agent (derived from Active Minerals); SP is a high-efficiency water-reducing agent (derived from KFDN).
[0038] Please see Figure 1 The figures show the compressive strength test results of three groups of 3D-printed concrete parts in three dimensions and their corresponding cast specimens in embodiments of the present invention. In each example, four strips with different patterns represent the three-dimensional directions x, y, and z, and their corresponding cast specimens. Compared to control group 2, the untreated recycled aggregate group, the 3D-printed concrete parts of the present invention showed the best and most significant enhancement in compressive strength test results. This can be attributed to the enhanced bonding between the recycled aggregate and the cementitious material due to the PVA-treated recycled aggregate.
[0039] Figure 2The figures show the flexural strength test results of three groups of 3D-printed concrete parts in the two-dimensional direction and their corresponding cast specimens in embodiments of the present invention. In each example, three strips with different patterns represent the two-dimensional directions y and z, and their corresponding cast specimens. Compared to control group 1 (without recycled aggregate), the embodiments of the 3D-printed concrete parts implemented according to the present invention show an increase in flexural strength.
[0040] Figure 3 This diagram shows the water absorption test results of three sets of 3D-printed concrete parts according to ASTM C642 in an embodiment of the present invention. The three bars represent each example. The embodiment of the 3D-printed concrete parts implemented according to the present invention also exhibits optimal performance in the water absorption test results.
[0041] Figure 4 This diagram shows the shrinkage test results of three sets of 3D-printed concrete parts in an embodiment of the present invention. The three broken lines represent each example. The broken line shown in the embodiment of the 3D-printed concrete parts implemented according to the present invention is the smoothest in the shrinkage test results after 7 days. Furthermore, Figure 5 This image shows the tensile strength test results of three sets of 3D-printed concrete parts after 28 days of bonding, according to an embodiment of the present invention. The three long bars represent each example. The embodiment of the 3D-printed concrete parts implemented according to the present invention still exhibits optimal performance in the tensile strength test results.
[0042] Figures 6A to 6D This is a schematic diagram illustrating the effect of PVA solution treatment on the 3D printing material composition in this invention. The treatment method involves coating a PVA film or thin film onto the outer layer of recycled aggregate, thereby improving the quality consistency of the 3D printing material composition. Furthermore, Figure 6D The recycled aggregates that have undergone intermediate processing are further coated with ordinary Portland cement (OPC), fly ash (PFA), and slag powder (GGBS), which can further improve their bonding with admixtures.
[0043] Figure 7 This is a flowchart of a method for processing a 3D printing material composition according to the present invention. An embodiment of the present invention provides a method for processing a 3D printing material composition, the steps of which include: (a) Provide a 5wt% to 15wt% polyvinyl alcohol (PVA) solution; (b) Mix the recycled aggregate with a 5 wt% to 15 wt% PVA solution and soak the mixed recycled aggregate for at least 24 hours; (c) The air-dried and mixed recycled aggregate is left to dry for at least 7 days to form treated recycled aggregate; (d) Mixing treated recycled aggregates with cementitious binders, aggregates, water and admixtures to form a composition of 3D printing materials.
[0044] Preferably, the 5wt% to 15wt% PVA solution is prepared by mixing PVA powder with water at 90°C to 100°C. The mixed recycled aggregate is then air-dried at 20°C.
[0045] Preferably, the optimal particle size of each recycled aggregate is between 0.3 mm and 2.36 mm. The recycled aggregate accounts for more than 30% of the total weight of the aggregate and the recycled aggregate.
[0046] In one embodiment of the present invention, the processing method of the 3D printing material composition is as follows. First, PVA powder is mixed with boiling water using an electric stirrer until a uniform mixture is obtained. Then, recycled aggregate with a particle size of 0.3-2.36 mm is added. The mixture is mixed again using an electric stirrer to ensure sufficient contact between the recycled aggregate and the PVA solution for about 10 to 15 minutes. The mixture is allowed to stand overnight, and after 24 hours it is spread out and air-dried at 20°C for 7 to 14 days. Finally, the treated recycled aggregate is prepared. The treated recycled aggregate is mixed with cementitious binder, aggregate, water, and admixtures to obtain the 3D printing material composition according to the present invention.
[0047] Figure 8A and Figure 8B The images show SEM images of regular recycled aggregate and recycled aggregate treated with PVA solution, respectively. Figure 8B In recycled aggregate treated with PVA solution, a distinct PVA film or agglomeration can be observed on the surface. In contrast, Figure 8A Untreated recycled aggregates in the middle only show some layered structure, which can be considered as old aggregate O and old cement matrix C.
[0048] The present invention has the following advantages: 1. The optimized composition of the 3D printing material contains at least 34% environmentally friendly materials (including recycled aggregates and low-carbon materials), and has excellent mechanical properties and durability. 2. Surface-treated recycled aggregate can replace up to 40% of conventional aggregate without affecting its mechanical properties. This innovation maintains the consistency of quality in 3D-printed concrete components and improves repeatability, printability, and constructability. Furthermore, compressive strength and flexural strength can reach over 30 MPa and 10 MPa, respectively. 3. By employing optimized recycled aggregate particle size distribution and processing methods, the shrinkage of 3D printed concrete parts is reduced to less than 900 με. 4. The formulation of the 3D printing material composition has been validated in large-scale printing projects (design size exceeding 1 meter) and implemented in the field under various conditions (including low temperature, high humidity, or low humidity environments).
Claims
1. A 3D printing material composition, said composition comprising a cementitious binder, aggregates, water, and admixtures; Its features are, The aggregate includes recycled aggregate and quartz sand, and the recycled aggregate is treated with a water-soluble polymer.
2. The composition according to claim 1, characterized in that, The water-soluble polymer is a polyvinyl alcohol (PVA) solution.
3. The composition according to claim 2, characterized in that, The PVA solution has a weight percentage concentration of 5 wt% to 15 wt%.
4. The composition according to claim 1, characterized in that, The water comprises 10% to 20% of the total weight of the composition.
5. The composition according to claim 4, characterized in that, The cement-based adhesive material accounts for 20% to 40% of the total weight of the composition and contains 50% to 70% cement.
6. The composition according to claim 4, characterized in that, The recycled aggregate accounts for 10% to 30% of the total weight of the composition, and the recycled aggregate accounts for more than 30% of the total weight of the aggregate.
7. The composition according to claim 4, characterized in that, The quartz sand accounts for 25% to 40% of the total weight of the composition.
8. The composition according to claim 1, characterized in that, Each of the recycled aggregates has a particle size of 0.3 mm to 2.36 mm.
9. The composition according to claim 1, characterized in that, Each of the quartz sands has a particle size of 0.3 mm to 0.6 mm.
10. The composition according to claim 1, characterized in that, The cement-based binder contains fly ash, silica fume and / or ground granulated blast furnace slag (GGBS).
11. The composition according to claim 1, characterized in that, The admixture includes water-reducing agent, thixotropic agent, viscosity modifier, retarder, and expanding agent.
12. The composition according to claim 11, characterized in that, The expanding agent is a low-dose expanding agent.
13. A method for processing a 3D printing material composition, comprising: (a) Provide a 5wt% to 15wt% polyvinyl alcohol (PVA) solution; (b) Mix the recycled aggregate with a 5 wt% to 15 wt% PVA solution and soak the mixed recycled aggregate for at least 24 hours; (c) The air-dried and mixed recycled aggregate is left to dry for at least 7 days to form treated recycled aggregate; (d) Mixing treated recycled aggregates with cementitious binders, aggregates, water and admixtures to form a composition of 3D printing materials.
14. The method as described in claim 13, characterized in that, The 5wt% to 15wt% PVA solution is prepared by mixing PVA powder with water at 90°C to 100°C.
15. The method as described in claim 13, characterized in that, The mixed recycled aggregate was air-dried at 20°C.
16. The method as described in claim 13, characterized in that, Each of the recycled aggregates has a particle size of 0.3 mm to 2.36 mm.
17. The method as described in claim 13, characterized in that, The recycled aggregate accounts for more than 30% of the total weight of the aggregate and the recycled aggregate.